Pemberdayaan Kelompok "POSYANDU LANSIA" Desa Medan Estate untuk Lansia PASTi (Produktif, Aktif, Sehat, Tangguh, dan Terlindungi) melalui Healthy Home Service - Riny Apriani; Puput Melati Hutahuruk; Jessi Gustina; Hafizullah Levi Zain; Irdina Bazla (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2025)
Many elderly residents receive insufficient attention from the health service side, so many elderly people are unaware that they suffer from high blood pressure, diabetes, gout and others. The purpose of community service is to empower the "Posyandu Lansia" group in Medan Estate village so that the elderly can become PASTi (Productive, Active, Healthy, Resilient, and Protected) through Healthy Home Service. The community service method to solve this problem is by empowering the posyandu group with an active participatory principle in the form of socialization and training. The location of implementation is the posyandu elderly in Medan Estate Percut Sei Tuan village. The results of this community service through pretests and posttests show an increase in the knowledge of elderly members. Posyandu cadres also experienced a significant increase in the use of health equipment